ANALISIS STRUKTUR DAN NILAI KEARIFAN LOKAL DALAM CERITA RAKYAT PERANG OBOR DI DESA TEGALSAMBI JEPARA - Mely Rohmawati; Tika Aniffartur Rif’ah; Siska Nadia Febrianti; Syaharani Naswa Natasya; Mohammad Kanzunnudin (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was designed to analyze the structure and value of local wisdom contained in the folklore "Perang Obor". This research uses descriptive qualitative method. This method was chosen because the data in the study were in the form of fragments of stories sourced from a book entitled "East Coast Folklore" totaling 230 pages written by Mohammad Kanzunnudin with 43 stories. This book was published in 2024 by CV. Adhigama. The story that the author analyzes is entitled "Obor War" which is found on pages 7 to 12. The theory used in structural analysis uses the theory of Alan Dundes. The analyzed structure consists of only five motifs including, lack (shortage), violation (violation), consequence (result caused), and attempted eascap (avoiding the consequences that occur), and Lack Liquidated (shortage can be overcome). The value of local wisdom using the theory of Sibarani which produces five of them, the value of commitment, the value of preservation, the value of gratitude, the value of education, and the value of hard work